High temperatures and workplace injuries - Matteo Picchio; Jan C. van Ours (Tinbergen Institute, 2024)
High temperatures can have a negative effect on workplace safety for a variety of reasons. Discomfort and reduced concentration caused by heat can lead to workers making mistakes and injuring themselves. Discomfort can also be an incentive for workers to report an injury that they would not have reported in the absence of heat. We investigate how temperature affects injuries of professional tennis players in outdoor singles matches. We find that for men injury rates increase with ambient temperatures. For women, there is no effect of high temperatures on injuries. Among male tennis players, there is some heterogeneity in the temperature effects, which seem to be influenced by incentives. Specifically, when a male player is losing at the beginning of a crucial (second) fourth set in (best-of-three) best-of-five matches, the temperature effect is much larger than when he is winning. In best-offive matches, which are more exhausting, this effect is age-dependent and stronger for older players.
Keywords: J24; J81; Q51; Q54; 330; Climate change; temperatures; tennis; injuries; health